Exploratory Factor Analysis for Developing Wheelchairs for Children with Cerebral Palsy - Rahmalina, Dwi; Ningtyas, Desinta Rahayu; Hidayah, Nur Yulianti; Suwandi, Agri; Zariatin, Dede Lia; Lesmana, I Gede Eka; Mahandika, Dhidik; Sudiro, Susanto (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2025)
A wheelchair is an essential mobility tool for individuals with limitations, including children with Cerebral Palsy (CP). Cerebral palsy affects children under five and causes stiffness in various body parts. The design of wheelchairs for children with CP differs significantly from standard wheelchairs, prompting this research to identify the key factors that should be considered in designing such wheelchairs. This study used exploratory factor analysis, data was gathered from children with CP and their caregivers in Java. The findings revealed six fundamental factors to consider when designing wheelchairs for children with CP: Main features, Ultimate comfort, standard compliance, robust durability, thoughtful ergonomics, unique special features, user-friendly design, and aesthetic appeal. In summary, while the main features are crucial in the design of wheelchairs for children with CP, it is equally important that these wheelchairs comply with applicable standards and incorporate special features tailored specifically for these young users.